Visco-hyperelastic model for soft rubber-like materials - P. Mohammed, Mohd Afandi (Penerbit Uniersiti Kebangsaan Malaysia, 2014)
This paper investigates the application of visco-hyperelastic model to soft rubberlike material, that is gluten. Gluten is a major protein in wheat flour dough (a mixture of flour and water) which exists as long network fibers and undergo large deformation under uniaxial tension and compression. The visco-hyperelastic model is represented by a combination of the viscoelastic Prony series and the hyperelastic extended tube model. Calibration of the visco-hyperelastic model to gluten tests result suggests that gluten can be modelled as a finite viscoelastic material.